Fire and memory : on architecture and energy - Fernández-Galiano, Luis (Writing architecture., 2000)
Galiano points out that energy, so important to the origins of architectural theory in Vitruvius's time, has been absent from such theory since the introduction of the "dictatorship of the eye" over the other senses. With Fire and Memory, he reintroduces energy to the discussion of architecture and reminds us that the sense of touch is as necessary to an understanding of the environment as the sense of sight."--Jacket.